2014
DOI: 10.1038/ncomms6748
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals dysregulation of innate immune response genes and neuronal activity-dependent genes in autism

Abstract: Recent studies of genomic variation associated with autism have suggested the existence of extreme heterogeneity. Large-scale transcriptomics should complement these results to identify core molecular pathways underlying autism. Here we report results from a large-scale RNA sequencing effort, utilizing region-matched autism and control brains to identify neuronal and microglial genes robustly dysregulated in autism cortical brain. Remarkably, we note that a gene expression module corresponding to M2-activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
472
3
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(512 citation statements)
references
References 58 publications
31
472
3
6
Order By: Relevance
“…All conditions were performed in triplicate for each dataset and were repeated three times (n = 3). Significance of comparisons was determined for stimulated cells and for those cells with inhibitors/flavonoids, as denoted by the horizontal lines (P < 0.001 or P < 0.0001), and also among each of the inhibitor/flavonoid treatments shown by the horizontal brackets and by the corresponding *P < 0.05, **P < 0.001, or ***P < 0.0001. between mast cells and microglia (15,87), found to be activated in brains of patients with ASD (8)(9)(10)(11)88), is implicated in inflammation of the brain (89).…”
Section: Discussionmentioning
confidence: 99%
“…All conditions were performed in triplicate for each dataset and were repeated three times (n = 3). Significance of comparisons was determined for stimulated cells and for those cells with inhibitors/flavonoids, as denoted by the horizontal lines (P < 0.001 or P < 0.0001), and also among each of the inhibitor/flavonoid treatments shown by the horizontal brackets and by the corresponding *P < 0.05, **P < 0.001, or ***P < 0.0001. between mast cells and microglia (15,87), found to be activated in brains of patients with ASD (8)(9)(10)(11)88), is implicated in inflammation of the brain (89).…”
Section: Discussionmentioning
confidence: 99%
“…Given their role in immune surveillance and debris clearance, it is perhaps unsurprising that microglial activation in particular has been implicated in neurodegenerative diseases beyond Alzheimer's disease, including multiple sclerosis and Parkinson's disease (Chung et al, 2015b;Heneka et al, 2015;Hong et al, 2016). As evidence accumulates positioning glia as critical for synapse maturity and elimination, many have speculated that glia and immune signaling are associated with many neuropsychiatric disorders, from stress-related conditions such as depression (Hodes et al, 2015;Miller and Raison, 2015), to neurodevelopmental disorders such as autism and schizophrenia (Gupta et al, 2014;Sekar et al, 2016;Werling et al, 2016). Here, we propose that microglia and astrocytes have an important yet largely unexplored role in the development and maintenance of drug addiction.…”
Section: Resultsmentioning
confidence: 99%
“…An extended transcriptome study of autism cortex also found upregulation of immune genes in autism specifically identifying increased expression of activated microglia genes. This study also identified misexpression of synaptic activity genes in autism [192]. To narrow down autism heterogeneity to the pathology of a specific development time point, cell type, and brain region, Willsey et al [193] analyzed expression data from several brain regions at many stages of development.…”
Section: Autism Genetic Studies May Point To Convergentmentioning
confidence: 93%